Performance management : integrating strategy execution, methodologies, risk, and analytics - Cokins, Gary (John Wiley & Sons, 2009)
Praise for Praise for Performance Management: Integrating Strategy Execution, Methodologies, Risk, and Analytics. "A highly accessible collection of essays on contemporary thinking in performance management. Readers will get excellent overviews on the Balanced Scorecard, strategy maps, incentives, management accounting, activity-based costing, customer lifetime value, and sustainable shareholder value creation.". Robert S. Kaplan, Harvard Business School; coauthor of The Balanced Scorecard: Translating Strategy into Action, The Execution Premium, and many other books. "Gary